PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL DAN PENGUNGKAPAN TANGGUNG JAWAB SOSIAL TERHADAP NILAI PERUSAHAAN - Vinny Febriani; Munawaroh (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
This study’s purpose was to analyze the effect of managerial ownership, institutional ownership, and Corporate Social Responsibility (CSR) disclosure on firm value to the consumer goods industry sector listed on the Indonesia Stock Exchange for 2017-2019. Using the purposive sampling method in its sample selection and yielded 26 companies. The results showed that partially institutional ownership and CSR disclosure positively affect firm value, managerial ownership is significantly negative, while simultaneously has positive effect.